THE FOCUS OF SOUTH AFRICAN ORGANISATIONS ON BRAND EQUITY AND CUSTOMER EQUITY - Frank, Natalie (My University, 2011)
Intangible assets are becoming an increasing portion of the value of organisations. Consequently, to grow Shareholder Value, management need to focus on building intangible assets, rather than a concentration on tangibles. However, as these are intangible and difficult to quantify, the temptation is to cut back on these assets to meet short term financial objectives. The purpose of the research was to evaluate the perception of South African marketers in determining their choice of marketing investments; whether to focus on building Brand Equity, Customer Equity or both through marketing programmes with a view to increasing Shareholder Value. The research set out to evaluate the rationale for investing in marketing assets and to ascertain the positioning of different industries on the marketing equity trade-off matrix. The research used a combination of quantitative and qualitative data. There were 60 respondents from a convenience sample who were marketing practitioners involved in the budget allocation decisions within their organisations. Quantitative data was analysed using the distribution-fitting rescaling analysis, a method demonstrating accuracy and validity. The qualitative data was content analysed using data reduction and data display to draw conclusions. The main findings show that the majority of marketing practitioners chose to focus on both concepts simultaneously; 64% of interviewees rated building Brand Equity as very important and 74% rated the same for building Customer Equity. Therefore the research findings suggest that the Brand and Customer Equity matrix proposed by Bick (2009) is the correct diagrammatic representation to use as opposed to a single-line spectrum. Brand building plays an important role in establishing a unique positioning and brand image by simplifying the consumer‟s purchase decision amongst competing brands. Customer Equity plays an important role in providing clear quantifiable financial effects, contributing to the bottom line and driving long term profitability and sustainability
MBA thesis - WBS
Keywords: Brands and branding; Customer equity